Studies of the physiological function of carbonic anhydrase - Peng, Chun-xia; Gao, Yan-ming (Beijing da xue xue bao. Journal of Peking University. Yi xue ban, 2007)
Carbonic anhydrases (CA) is a zinc-enzyme family. They are involved in multiple aspects of systemic and cellular acid-base balance. This review is a general introduction to the disposition, molecular constitution,biological function and physiological function of CA.